Development of Heating and Cooling Systems for Athletes in Extreme Sports Sport Combat: A Literature Review - Nimrot Manalu; Maelan Dwi br Banurea; Maharani Putri Hasibuan; Juni Yanti Nasution (Joska: Jurnal Isori Kampar, 2025)
Objectives: This literature review examines the current state of heating and cooling systems designed for athletes participating in extreme combat sports, evaluating their effectiveness in managing core body temperature and enhancing performance under thermal stress conditions. Methods: A systematic literature review was conducted using multiple academic databases to identify studies on thermal management systems for combat sports athletes. Search criteria included peer-reviewed articles published between 2019-2025 focusing on cooling and heating technologies, heat acclimation protocols, and performance outcomes in combat sports environments. Results: The review identified multiple thermal management approaches including palm-based cooling systems, isothermic heat acclimation protocols, and external cooling strategies. Central cooling methods demonstrated superior effectiveness (SMD = 0.43, 95% CI 0.27 to 0.58, p < 0.001) compared to peripheral cooling approaches4. Palm cooling technologies utilizing arteriovenous anastomoses showed promise for rapid core temperature regulation in combat sports. Conclusion: Current thermal management systems show significant potential for enhancing combat sports performance, with central cooling strategies proving most effective. However, research gaps exist regarding optimal protocols for specific combat sports and long-term adaptation effects.